2012
DOI: 10.1007/s00439-012-1175-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced interferon (IFN)-α conditioned by IFNA2 (−173) and IFNA8 (−884) haplotypes is associated with enhanced susceptibility to severe malarial anemia and longitudinal all-cause mortality

Abstract: Severe malarial anemia (SMA) is a leading cause of pediatric morbidity and mortality in holoendemic Plasmodium falciparum transmission areas. Although dysregulation in cytokine production is an important etiology of SMA, the role of IFN-α in SMA has not been reported. As such, we investigated the relationship between IFN-α promoter polymorphisms [i.e., IFNA2 (A-173T) and IFNA8 (T-884A)], SMA, and functional changes in IFN-α production in children (n=663; <36 mos.) residing in a holoendemic P. falciparum transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Variations at IFN-α promoter (17470-G/G and L168V-G/G genotypes) or receptor IFNAR1 were associated with protection against severe malaria (43,46), whereas variation at IFNA2-173 and IFNA8-884 reduced IFN-α production and increased susceptibility to severe malarial anemia and mortality (44). Here we showed that the IFN responses to two strains of P. yoelii infection were dramatically different, with mice infected with N67 producing higher IFN-I response than those infected with N67C, whereas mice infected with N67C had higher IFN-γ transcript levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations at IFN-α promoter (17470-G/G and L168V-G/G genotypes) or receptor IFNAR1 were associated with protection against severe malaria (43,46), whereas variation at IFNA2-173 and IFNA8-884 reduced IFN-α production and increased susceptibility to severe malarial anemia and mortality (44). Here we showed that the IFN responses to two strains of P. yoelii infection were dramatically different, with mice infected with N67 producing higher IFN-I response than those infected with N67C, whereas mice infected with N67C had higher IFN-γ transcript levels.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-I and -II responses and the related pathways have been shown to play an important role in controlling malaria parasite infection (12,42), but the exact effects of the IFN on malaria infection remain to be clearly defined (22,(43)(44)(45). Daily injections of a recombinant human IFN-α prevented death by PbANKA cerebral malaria (45), and the majority of ifnar1…”
Section: Discussionmentioning
confidence: 99%
“…The core motif for PR-A and PR-B binding is ttaTgtt and the core recognition motif for c-Myb is ttaAgtt thus suggesting that the polymorphism might alter the binding of these transcription factors and thus influence disease outcome. TA genotype of rs10964981 (T/A) is associated with significantly lower circulating IFNa levels and a higher risk of developing severe malarial anaemia (SMA) in Gabonese children (Kempaiah et al, 2012). However genetic association results in our study show an inverse relationship with association of the TA genotype with protection from disease in the non-endemic region.…”
Section: Polymorphisms Of Ifna and Ifnar1 And Diseasementioning
confidence: 69%
“…Genetic variations/polymorphisms in IFNG, IFNGR1, IFNA cluster and IFNAR1 were selected according to their reported functional relevance in falciparum malaria as well as other infectious diseases, in other world populations (Kempaiah et al, 2012;Khor et al, 2007;Koch et al, 2006Koch et al, , 2005. A total of 24 polymorphisms were selected for the four genes.…”
Section: Selection Of Polymorphic Loci For Disease Associationmentioning
confidence: 99%
See 1 more Smart Citation